VARIAÇÃO DIÁRIA DA COMPOSIÇÃO DO LEITE DE VACAS DA RAÇA JERSEY NO PERÍODO DE VERÃO - Farias, Joana d. M.; Zenzen, Angelo M.; Juswiak, Patrícia; Pagnussat, Gabriela; Kuinchtner, Bruno C.; Diefenbach, Jairo; Richards, Neila S. P. d. S.; Sartori, Cesar O.; Maixner, Adriano R.; Berto, Jorge L. (Salão do Conhecimento, 2013)
Resumo